NON-INFECTIOUS ANTERIOR UVEITIS IN CHILDREN - A REVIEW OF THE LITERATURE - Velkovska B; Trpevska Shekerinov N; Kjaeva Nivichka J; Ivanova Cekov M; Petrushevska A (Department of Anaesthesia and Reanimation, Faculty of Medicine, “Ss. Cyril and Methodius” University in Skopje, R.N.Macedonia, 2022)
Introduction: Uveitis is a challenging condition for ophthalmologists to treat, and it is considerably more challenging when the patient is a child. Childhood uveitis is rather common, yet many cases go misdiagnosed due to the child’s lack of cooperation, lack of subjective symptoms, non-expression of subjective symptoms, parental lack of information, and so on. The purpose of this study is to highlight the most prevalent types of anterior uveitis in children, describe the most common clinical entities, and emphasize the significance of regular and thorough examinations of children who visit ophthalmology clinics. Conclusion: While childhood uveitis is a challenging pathology for ophthalmologists to treat, the fact that there are many protocols for diagnosis and therapy, makes the ophthalmologist’s job easier and gives him confidence in which way to go. The need of regular ophthalmological examinations in childhood, bio-microscopy, and fundus inspection in mydriasis cannot be overstated.
Keywords: children; non-infectious; uveitis